Discrete Laplace as applied to the SWGDAM-compliant U.S. subpopulations in the Y Chromosome Haplotype Reference Database. (December 2022) - Letts, Brandon; Myers, Steven; Askew, Christopher; Barritt-Ross, Suzanne; Gross, Ann Marie; Peters, Dixie; Roewer, Lutz; Wallin, Jeanette; Willuweit, Sascha
Abstract: Late in 2021, the Y Chromosome Haplotype Reference Database (YHRD) added the capability to perform discrete Laplace statistical calculations on searches performed against their SWGDAM-compliant U.S. subpopulations. Because discrete Laplace is not a commonly used or reported statistic in the United States, the SWGDAM Lineage Marker Committee, responsible for maintaining the SWGDAM Interpretation Guidelines for Y-Chromosome STR Testing, evaluated the feature to assess its ease of use and applicability to U.S. casework. Discrete Laplace calculates profile probabilities based on their genetic distance from sets of ancestral alleles and can yield much more informative probability estimates than the commonly used Clopper-Pearson 95% upper confidence interval (UCI). This is especially true for rare profiles with no database observations because, unlike the 95% UCI, the discrete Laplace calculation is not based upon how many times a profile is observed in the database. However, the statistic as applied by YHRD also has some limitations, such as a requirement that the query profile is complete for the 'minimal' kit and that expanded loci beyond those included in the Y17 kit cannot be included in the calculation. Here, we explain how discrete Laplace works and demonstrate how the results compare to those generated using the 95% UCI.